Subcutaneous ICD Proven Safe and Effective - Buckley, Rita (MD Conference Express, 2012)
An investigational, fully subcutaneous implantable cardioverter defibrillator (S-ICD) that senses, detects, and treats malignant ventricular tachyarrhythmias exceeded prespecified safety and efficacy endpoints in a recent clinical trial, potentially paving the way for a paradigm shift in ICD technology.